Forest and silvopastoral cover changes and its drivers in northern Morocco. (December 2018) - Chebli, Youssef; Chentouf, Mouad; Ozer, Pierre; Hornick, Jean-Luk; Cabaraux, Jean-François
Abstract: In northern Morocco, forest and silvopastoral areas have always formed an integral part of goat feeding and consequently of extensive livestock systems. However, it was reported that these areas are now going through a gradual degradation mainly due to overgrazing, resulting in land use-land cover (LULC) changes. Doubts persist about actual goat grazing impacts on forest and silvopastoral cover changes. Detecting and understanding drivers of LULC changes has become a central component of current strategies for managing natural resources to implement appropriate development policies. The objectives of this study were to assess the forest and silvopastoral cover changes and transition among five major land cover classes that took place in the last three decades (1984–2014), to verify the hypothesis that goats act as a main driver of forest and silvopastoral degradation, and to explore the perception of stakeholders based on remote sensing data, field surveys, and overall statistics. Between 1984 and 2014, forest and silvopastoral areas declined by 25% (matorral included). Farmers and local institutions all agreed that drought, fire, soil erosion, and population growth are the most striking drivers of forest and silvopastoral decreases. One being utilitarian and the other protectionist, they have conflicting perceptions about the effect of agricultural expansion, authority policy, deforestation, and overgrazing. The forest cover change is impacted by interaction among different change drivers. The levels of forest degradation depend on the intensity of this interaction. The outcomes confirm the alarming decrease in the amount of forest and silvopastoral cover. These results can be used as the first guide for future studies and decision-makers, focusing on the real drivers of forest and silvopastoral degradation, so as to develop targeted intervention to secure sustainable and sufficient resources needed for animal and population well-being. Highlights: Land cover changes in northern Morocco between 1984 and 2014 were studied. Forest and silvopastoral areas declined over the last 30 years. Main drivers of land cover changes were identified. Perception of stakeholders about drivers of land cover changes was explored. Socio-economic and ecological studies are needed to examine the impacts of LULC changes.